Case Report: Deficiency of Adenosine Deaminase 2 (DADA2) as a Cause of Brainstem Stroke in a 3-Year-Old Girl and the Importance of Early Fast-Track Genetic Diagnostics to Influence Therapy - Gburek-Augustat, Janina; Platzer, Konrad; Schumann, Isabell; Starke, Sven; Hershfield, Michael Steven; Sorge, Ina; Merkenschlager, Andreas (Neuropediatrics, 2022)
Deficiency of adenosine deaminase 2 (DADA2) is a rare Mendelian, autoinflammatory multiorgan disease. We report the case of a 3.8-year-old female patient who was admitted with an acute brainstem stroke and was diagnosed with DADA2 by early initiation of exome sequencing. We recommend that DADA2 and a genetic workup should be taken into account, when evaluating strokes in children even if no other than neurological symptoms are evident.
Keywords: DADA2; fast-track exome sequencing; inflammation; vasculitis; brainstem; early stroke